The Impact of E-Service Quality on User Loyalty of Digital Farming Applications in Tuban Regency, Jawa Timur Province, Indonesia - Sihombing, Maruli Tua; Hubeis, Musa; Cahyadi, Eko Ruddy (Universitas Panji Sakti, 2025)
The advent of digital technologies has significantly impacted various sectors, including agriculture. The study addresses the impact of e-service quality on digital farming application adoption, which is crucial for agricultural transformation. Utilizing a Structural Equation Model (SEM) analysis through SmartPLS, we examined constructs such as Efficiency, System Availability, Fulfillment, Privacy, User Satisfaction, and User Loyalty. The research was conducted from March to April 2024 with 124 smallholder farmers as respondents, using a purposive sampling technique. The analysis revealed that Efficiency increases user satisfaction by 40%, while System Availability enhances it by 44.3%, ultimately increasing loyalty by 84.5%. Privacy also positively impacts User Satisfaction, albeit marginally. These results underscore the importance of high e-service quality in fostering user satisfaction and long-term loyalty. This study recommends that developers improve system reliability, enhance efficiency with AI-driven support, and strengthen data security measures. Policymakers should support digital literacy programs and foster public-private partnerships to encourage wider adoption of digital technologies. These steps can improve user engagement, retention, and long-term success of digital farming applications. This study highlights the potential of digital farming applications to transform agriculture by promoting sustainable practices and improving farmer livelihoods through enhanced user satisfaction and loyalty.